INTEREST IN PARTICIPATING MARTIAL SPORTS RIVIEWED FROM THE NUTRITIOMAL STATUS OF JUNIOR HIGH SCHOOL STUDENTS IN THE CITY OF GORONTALO - Putra, Edy Dharma; Haryani, Meri; Kadir, Suprianto (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Students' interest in taking part in Martial Arts is still an important thing in recruiting student athletes. The purpose of this research is to understand the students' interest in participating in martial arts sports by considering the interest in participating in martial arts sports. This study uses a quantitative method by analyzing a simple correlation relationship. The population sample in this study was junior high school students from 9 districts in Gorontalo City, which consisted of 22 junior high schools (16 public junior high schools and 6 private junior high schools). The sample is taken as a whole (Total Sampling). Data was collected by distributing questionnaires about interest in participating in martial arts and tests to measure interest in participating in martial arts. Data analysis included descriptive analysis, homogeneity and normality tests, as well as simple correlation hypothesis testing and t tests to test significance. The results showed that the correlation coefficient (ryx₁) was 0.799 with a significance of p <0.05. This shows that there is a significant effect of nutritional status on students' interest in participating in martial arts. The Nutritional Status variable contributed 63.9% (R^2 = 0.639) to students' interest in participating in Martial Arts, while the remaining 36.1% was influenced by other factors.